To find the composite function that converts temperatures from degrees Kelvin to degrees Fahrenheit, we start with the two functions given:
-
From Kelvin to Celsius: \[ C(x) = x - 273.15 \]
-
From Celsius to Fahrenheit: \[ F(x) = \frac{9}{5}x + 32 \]
To create the composite function \( F(C(x)) \), which converts Kelvin to Fahrenheit, we substitute \( C(x) \) into \( F(x) \):
-
Substitute \( C(x) = x - 273.15 \) into \( F(x) \): \[ F(C(x)) = F(x - 273.15) = \frac{9}{5}(x - 273.15) + 32 \]
-
Now simplify the expression: \[ F(C(x)) = \frac{9}{5}(x - 273.15) + 32 \] \[ = \frac{9}{5}x - \frac{9}{5} \cdot 273.15 + 32 \] \[ = \frac{9}{5}x - 490.07 + 32 \] \[ = \frac{9}{5}x - 458.07 \]
Now, looking at the response options, we need the version that expresses this whole process correctly, which is: \[ \left( C \circ F \right)(x) = \frac{9}{5}(x - 273.15) + 32 \]
Thus, the correct composite function that converts Kelvin to Fahrenheit is: \[ \left( F \circ C \right)(x) = \frac{9}{5}(x - 273.15) + 32 \]
Matching it with the provided options, the correct one would be: \[ \boxed{\left( C \circ F \right)(x) = \frac{9}{5}(x - 273.15) + 32} \]